N6-Methyladenosine: a conformational marker that regulates the substrate specificity of human demethylases FTO and ALKBH5 - Zou, Shui (2018)
N6-Methyladenosine (m6A) is currently one of the most intensively studied post-transcriptional modifications in RNA. Due to its critical role in epigenetics and physiological links to several human diseases, it is also of tremendous biological and medical interest. The m6A mark is dynamically reversed by human demethylases FTO and ALKBH5, however the mechanism by which these enzymes selectively recognise their target transcripts remains unclear. Here, we report combined biophysical and biochemical studies on the specificity determinants of m6A demethylases, which led to the identification of an m6A-mediated substrate discrimination mechanism. Our results reveal that m6A itself serves as a ‘conformational marker’, which induces different conformational outcomes in RNAs depending on sequence context. This critically impacts its interactions with several m6A-recognising proteins, including FTO and ALKBH5. Remarkably, through the RNA-remodelling effects of m6A, the demethylases were able to discriminate substrates with very similar nucleotide sequences. Our findings provide novel insights into the biological functions of m6A modifications. The mechanism identified in this work is likely of significance to other m6A-recognising proteins.